PATHOGENETIC JUSTIFICATION AND EFFICIENCY OF MELATONIN APPLICATION IN PATIENTS WITH BRONCHIAL ASTHMA - G. I. Litvinenko; A. V. Shurlygina; V. S. Shirinsky; V. M. Nepomnjаshih; I. V. Shirinsky; V. A. Trufakin (Медицинская иммунология, 2014)
Abstract. Present study dealt with efficiency of melatonin implementation in a combination therapeutic schedule of bronchial asthma (BA). A group of 248 patients with atopic, or mixed clinical forms of BA being in exacerbation, or medication remission state, and 36 healthy donors were included into the study. Melatonin (Melaxen, Unifarm, USA) was administered as a single daily dose of 0.003 g, at 21.00, accompanied by a standard therapy in twenty BA patients for 21 days. We determined contents and functional properties of Т- and B-lymphocytes, mononuclear phagocytes, IgE, IL-4, IFNγ levels, as well as melatonin concentrations in blood serum in the morning and evening time. When included into BA treatment protocol, melatonin proved to cause partial restoration of circadian rhythm for Tand B cell subpopulations, mononuclear phagocytes, cytokine production, due to its chronotropic and immunomodulating activity. This effect is associated with a more pronounced clinical effect, thus presuming reversibility of desynchronosis state.